Propagation Of Rayleigh Waves In Non-Homogeneous Orthotropic Half Space Elastic Media Under The Effect Of Magnetic Field - Rajneesh Kakar (Institute of Advanced Engineering and Science, 2013)
The influence of magnetic field on the propagation of Rayleigh waves in an inhomogeneous, orthotropic elastic solid medium has been discussed. The method of variable separation of is used to find the frequency equation of the surface waves. The obtained dispersion equations are in agreement with the classical results when magnetic field and non-homogeneity are neglected.